ANALISIS DAMPAK MEDIA SOSIAL TERHADAP ETIKA REMAJA - Takdir, Hadmirathi; Fauziah, Rezha; sabaruddin, sabaruddin (SOSIORELIGIUS, 2024)
Social media is one of the trends that cannot be separated from the lives of society, especially among teenagers. This research aims to analyze the influence of social media on teenage ethics in the city of Palopo according to Islam. In today's digital era, social media plays a significant role in the daily lives of teenagers, such as influencing their behavior. The purpose of this research is to understand the ethical forms of some teenagers in the city of Palopo and how social media impacts the ethics of these teenagers. The method used in this research is descriptive method with a qualitative approach, collecting data through interviews and in-depth observations. The results of the research indicate that the ethical forms of teenagers in the community of Palopo city vary, some have good ethics while others still have poor ethics. Meanwhile, the use of social media has a significant impact on the lives of some teenagers in Palopo city, both positive and negative. From an Islamic perspective, it is found that some teenage behaviors on social media often contradict the ethical values ​​in Islam. However, social media also has a positive impact as an effective educational platform if utilized properly. Keywords: Social Media, Teenage Ethics